A construção de um herói nacional pela grande mídia e suas implicações políticas - Nascimento, Janaina Cicari Astorino (Universidade Federal de São Carlos, 2023)
Most Political Science theorists attribute a unique role to the mainstream media in maintaining modern democracy. The present work aims to analyze the journalistic discourse about the Judiciary Field, from the perspectives of agenda setting and framing, identifying the process of construction of the figure of Sergio Moro as a national hero and his subsequent decline, as well as the relationship of this process with phenomena specific to Law, such as Judicial Activism, Judicialization of Politics and Politicization of the Judiciary. The method used was the Case Study, using the concepts already mentioned. It was possible to verify a direct relationship between the construction of this public figure and the phenomena of agenda setting and framing.
The construction of a national hero by the mainstream media and its political implications
Keywords: Comunicação social; Direito; Opinião pública; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO